2018
DOI: 10.1186/s12957-018-1454-y
|View full text |Cite
|
Sign up to set email alerts
|

A 0.8-cm clear cell neuroendocrine tumor G1 of the gallbladder with lymph node metastasis: a case report

Abstract: BackgroundNeuroendocrine tumors (NETs) of the gallbladder are rare and generally considered low-grade malignancies. We herein describe a case of a patient with a 0.8-cm clear cell NET G1 of the gallbladder with nodal involvement.Case presentationA 65-year-old man with no medical history indicative of von Hippel-Lindau (VHL) disease underwent laparoscopic cholecystectomy for cholecystolithiasis. There was a 0.8-cm tumor in the neck of the gallbladder. Histologic examination revealed nests or trabecular growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…A few case reports have been published on the different histologic types of GB-NEN, including neuroendocrine carcinoma, LCNEC, SCC, MANEC, carcinoid tumors, and atypical carcinoid tumors (12, 13, 14, 15, 16, 17, 18, 19). A previous study of GB-NEN cases from the SEER database between 2000 and 2005 reported that among 105 GB-NEN cases, 1% were LCNEC, 30.5% were SCC, 32.4% were carcinoid tumors, 34.3% were neuroendocrine carcinoma, and 1.9% were MANEC (7).…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports have been published on the different histologic types of GB-NEN, including neuroendocrine carcinoma, LCNEC, SCC, MANEC, carcinoid tumors, and atypical carcinoid tumors (12, 13, 14, 15, 16, 17, 18, 19). A previous study of GB-NEN cases from the SEER database between 2000 and 2005 reported that among 105 GB-NEN cases, 1% were LCNEC, 30.5% were SCC, 32.4% were carcinoid tumors, 34.3% were neuroendocrine carcinoma, and 1.9% were MANEC (7).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of a radical resection is to eliminate lesions, confirm a clear diagnosis, provide a basis for post-operative comprehensive treatment and improve the quality of life of affected patients (33). Surgical methods include simple, radical and expanded radical cholecystectomy, whereby the choice of surgical type is often discussed between the medical professional and patient (44). The progress made in recent years to expand the time period during which radical resection can be performed, including R0 resection for GB-NEC, has increased the overall long-term survival time of patients (31).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Preoperative diagnosis often depends on the typical oncoid syndrome. Since GB-NEN and oncoid syndrome are not associated, patients typically visit the doctor only during middle-or late-stage presentation with metastasis (44). Therefore, to increase the diagnosis rate and prevent progression of GB-NEN, an appropriate treatment is advised following complete routine examination for all patients with chronic cholecystitis and cholecystolithiasis.…”
Section: Preventionmentioning
confidence: 99%
“…These observations indicate that the risk of metastasis increases with increase in tumor size. Conversely, Hirose et al reported that even G1 tumors of extremely small size (≤1 cm) metastasize to the gallbladder lymph nodes, and extended additional surgery is required in such cases (13). In general, in cases of gastrointestinal and pancreatic NETs, high mitotic counts, high Ki-67 proliferation index values, large tumor diameters, and high invasion depths are considered risk factors for the existence of lymph node or distant metastasis (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no evidence regarding the efficacy of extended surgery or adjuvant chemotherapy in GB-NET G1 and G2 cases (17). If metastasis is observed during the histopathological examination of the cystic duct node, it should be determined whether a radical second resection with regional lymphadenectomy is the appropriate treatment of choice (13). In cases with cystic duct lymph node metastasis, radical second resection with lymph node dissection should be considered as an option for accurate nodal evaluation, based on the reported outcomes of incidental gallbladder cancer (18).…”
Section: Discussionmentioning
confidence: 99%